Increasing The Growth Of Oil Palm Seeds by Administering Various Types and Dosages of Organic Fertilizer in The Main Nursery - Jogi Andre Rigel; Neny Andayani; Erick Firmansyah (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Oil palm seedlings can be grown using either organic or inorganic fertilization; however, organic fertilization is more environmentally beneficial. This study seeks to determine the impact of organic fertilizer type and dosage on the growth of oil palm seedlings in the main nursery. This investigation employed a two-factor factorial experimental method arranged in a completely randomized design (CRD). The form of organic fertilizer consists of three levels: banana stems, water hyacinth, and manure. The second factor is the organic fertilizer dosage, which consists of three levels: 100g, 250g, and 300g. Five repetitions yielded nine treatment combinations and one control treatment (plants without organic fertilizer ) from these treatments. Observations included plant height, leaf count, stem diameter, fresh crown weight, dried shoot weight, root length, fresh root weight, dry root weight, and root volume. The results demonstrated a significant interaction between the type and dosage of organic fertilizer on the parameters of plant height, root length, shoot fresh weight, root fresh weight, and root volume. The combination that yields the greatest results is 300 grams of manure. Applying organic fertilizer in varying quantities results in superior plant growth compared to the control (without organic fertilizer ).